(untitled) (Palaeohispanica. Revista sobre lenguas y culturas de la Hispania Antigua, 2025)
This article pays homage to the international cooperation and interdisciplinarity that have characterised the first 50 years of the Palaeohispanic congresses. It presents some of the highlights and lessons learnt from working on the epigraphy and writing equipment of the Iberian peninsula in the context of a recent project, LatinNow, which explored Latinization, local languages, and literacies. We acknowledge the gap between ‘historical grand narratives’ and the realities on the ground, and the importance of controlling multiple scales of analysis and appreciating the local voices and communities in recovering ‘regionality’. New projects focused on the Peninsula exploiting so-called ‘épigraphie mineure’ and writing equipment, and the implementation of FAIR principles in our datasets, should assist us in recovering the local communities, complex epigraphic practices, shifting linguistic landscapes, and regional varieties of Latin in more detail. We sound a note of optimism for the future of our shared endeavours over the next fifty years.